Obesity and Body Fat Distribution as Coronary Risk Factors and Supply of Proinflammatory Cytokines - Oliveira,Andreia (2010)
The role of obesity on coronary heart disease risk is not fully understood; some studies have found linear associations while others have reported J- or U-shaped associations or even no significant effects, which could be related to the use of different measures of obesity. The amount and type of body fat distribution (frequently assessed by waist circumference or waist-to-hip ratio) were found to be better predictors of cardiovascular morbidity and mortality than total body weight and overall obesity, often measured by body mass index. Visceral and subcutaneous fat (both included when waist circumference is measured) have been frequently associated to metabolic complications, but only a few studies have addressed the cardiovascular role of peripheral fat mass (fat located in upper and lower limbs), which might be less atherogenic than abdominal fat, due to a low fatty acid turn-over and a differential hormone production. Moreover, a gender-effect may be present, but further research is needed to confirm it. The same associations reported with cardiovascular risk have been found with low-grade chronic inflammation. Adipose tissue is a known source of pro-inflammatory cytokines, and measures of central obesity seem to be stronger and more consistent predictors of inflammation than overall obesity. From this review, further metabolic studies to clarify how sex hormones may modulate the way in which fat is accumulated and stored and how it could influence the production of adipokines are warranted. Also, longitudinal research is needed to confirm the potential sex effect on the relation of peripheral fat with coronary risk (protective in women and adverse in men).